Promotion Strategy To Increase Engagement Through Instagram At Beeje Coffee Lhokseumawe - Anwar, Anwar; Raseki, Gebrina; Elvina, Elvina; Hakim, Lukman (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research aims to analyze Instagram-based promotional strategies used by Beeje Coffee Lhokseumawe in increasing customer engagement. In the digital era, social media marketing has become essential for small businesses, especially those in the culinary industry. This qualitative descriptive study utilized interviews, observation, and documentation to examine how Beeje Coffee crafts its promotional content, utilizes Instagram features, and addresses limitations in digital engagement. The findings reveal that visual consistency, creative content, and audience interactivity significantly impact engagement metrics. However, the absence of structured planning and limited digital skills remain major obstacles. The study is supported by theories of promotional strategy, digital marketing, social media utilization, Instagram branding, and digital engagement.